Infectious foodborne disease outbreaks and sporadic cases in Saudi Arabia: A 2017–2023 trend analysis - Alfaleh, Amjad; Alkattan, Abdullah; Alzaher, Abrar; Sagor, Khlood; Almarshoud, Saud; Ibrahim, Mona H. (Infectious diseases now (Online), 2025)
•A total of 42,079 infectious foodborne cases were reported in Saudi Arabia during 2017–2023.•The overall mean crude incidence rate for foodborne cases was 18.0 ± 5.7 per 100,000.•There were 12,710 cases related to foodborne outbreaks, while other cases (N = 29,369) were recognized as sporadic.•The most commonly detected pathogens were Entamoeba spp. (N=14,796) and Salmonella spp. (N=13,130). The present study aims to precisely indicate the status of infectious foodborne disease in Saudi Arabia between 2017 and 2023. A trend analysis was conducted based on epidemiologic data in Saudi Arabia during 2017–2023. The data include reports from governmental and private health agencies regarding Saudi citizens and residents, whatever their ages, who were diagnosed with infectious foodborne disease. Outbreak and sporadic patients were evaluated. Saudi Arabian crude incidence rates per 100,000 inhabitants and foodborne pathogens were established. All in all, 42,079 infectious foodborne illnesses were reported in Saudi Arabia between 2017 and 2023; the crude incidence rate averaged 18.0 ± 5.7 per 100,000. In 2017–2023, there were 12,710 foodborne outbreaks with a mean incidence rate of 5.4 ± 2.2 per 100,000. Results also indicate 29,369 sporadic cases reported during 2017–2023, with a mean crude incidence rate of 12.6 ± 3.9 per 100,000. The most widely described pathogen was Entamoeba spp. (mean crude incidence rate of 6.3 per 100,000), followed by Salmonella spp. (5.6 per 100,000), Hepatitis A virus (0.5 per 100,000), and Shigella spp. (0.2 per 100,000). This research presents trends regarding for confirmed infectious foodborne cases in Saudi regions from 2017 to 2023. Outbreak-related and sporadic cases have decreased in recent years. Given the high incidence of Entamoeba and Salmonella spp. in foodborne sporadic cases, health agencies are called upon to use diagnostic tools for frequently reported microbes in view of identifying and locating foodborne outbreaks.